The Effect of PhET Simulation Learning Media to Improve Science Proses Skills - Vira Gusvianti; Rudi Haryadi; Yus Rama Denny Muchtar (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Students are expected to be able to fulfill physics learning objectives according to the basic abilities established by process skills training. Furthermore, this research aims to determine how PhET media influences student learning outcomes for constant acceleration and uniform acceleration concepts. Thinking when solving problems, facilitating group or individual searches, facilitating conversations between students to motivate them to acquire knowledge, and assessing the problem-solving process. Non-equivalent Control Group Research is a type that is conducted. This design is very similar to a pretest-posttest control group design, except that the experimental and control groups are not randomly selected. After analyzing the data in Excel, continue with SPSS. Based on the research results, the control group that used traditional learning materials had an average posttest score of 67. In contrast, the experimental class that used PhET learning materials to improve student learning outcomes had an average posttest score of 78.